2006
DOI: 10.1128/aem.72.2.1380-1387.2006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacies of Disinfectants To Control Microbial Contamination in Dental Unit Water Systems in General Dental Practices across the European Union

Abstract: Water delivered by dental unit water systems (DUWS) in general dental practices can harbor high numbers of bacteria, including opportunistic pathogens. Biofilms on tubing within DUWS provide a reservoir for microorganisms and should be controlled. This study compared disinfection products for their ability to meet the American Dental Association's guideline of <200 CFU · ml ؊1 for DUWS water. Alpron, BioBlue, Dentosept, Oxygenal, Sanosil, Sterilex Ultra, and Ster4Spray were tested in DUWS (n ‫؍‬ 134) in Denmar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
70
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 46 publications
9
70
0
5
Order By: Relevance
“…We found that total effectiveness of 0.5% sodium hypochlorite was higher than Sanosil 6% and 2%. This is similar to the results of Ghahramanloo, which showed a superior antibacterial effect of 0.525% sodium hypochlorite spray over Sanosil solution (13).According to one report, Sanosil was more effective to disinfect environment surface including dental seat and office cabinets (14).Effectiveness of this material in removal of water contamination in dental units is also shown (15) . Sanosil has been reported to be effective on Alginate materials (13).…”
Section: Discussionsupporting
confidence: 83%
“…We found that total effectiveness of 0.5% sodium hypochlorite was higher than Sanosil 6% and 2%. This is similar to the results of Ghahramanloo, which showed a superior antibacterial effect of 0.525% sodium hypochlorite spray over Sanosil solution (13).According to one report, Sanosil was more effective to disinfect environment surface including dental seat and office cabinets (14).Effectiveness of this material in removal of water contamination in dental units is also shown (15) . Sanosil has been reported to be effective on Alginate materials (13).…”
Section: Discussionsupporting
confidence: 83%
“…Currently, there is no evidence based protocol for dentist to control the microbial quality of water from DUWLs (Liaqat & Sabri 2011;Schel et al 2006;Walker et al 2000). Distilled water does not prevent biofilm formation in DUWLs without proper and regular maintainence (Kettering et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Researches that have been done in many countries showed that microorganism contamination of DUWLs is a problem (Al-Hiyasat 2007;Blake 1963;Ma et al 2012;Mavridou et al 2006;Schel et al 2006;Singh et al 2003). Various microorganisms have been isolated from DUWLs, including environmental bacteria and human pathogens such as Pseudomonas (Al-Hiyasat et al 2007;Ma et al 2012;Mavridou et al 2006), Legionella pneumophila Walker et al 2000), Mycobacterium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Before NHSN opened enrollment to all facilities, its forerunner (the National Nosocomial Infections Surveillance system) was known to overrepresent large academic centers, and few other study groups focused on smaller hospitals. 7,8 NHSN now serves as the major secure data network for statewide mandatory public reporting programs, so accurate classification of teaching status is important to ensure fair representation of all hospitals. Hospitals joining NHSN fill in a survey screen that asks them to indicate whether they are affiliated with a medical school (yes or no) and, if yes, to characterize their involvement as one of the following 3 types: (1) major (facility is an important part of the teaching program of the medical school, and the majority of medical students rotated through multiple clinical services), (2) graduate (facility is used by the medical school for graduate training programs only-that is, residency and/or fellowships), or (3) limited (facility is used in the medical school's teaching program to a limited extent only).…”
Section: Validity Of Self-declared Teaching Status In Mandatory Publimentioning
confidence: 99%
“…However, the risk of infection among dental patients and healthcare personnel exposed to water contaminated by these microorganisms is minimal, because the bacterial load produced during therapy and their spread in the environment is low. 6 Nevertheless, most guidelines recommend disinfection of dental unit waterlines, 7 thus posing a risk of toxic effects.…”
mentioning
confidence: 99%